DEVELOPING ENGLISH SYLLABUS FOR STUDENTS AT MANAGEMENT AND INFORMATICS COMPUTER ACADEMY - Yuniarti, Yuti (CV. Ridwan Publisher, 2017)
The need of English is very crucial in the era of globalization nowadays. In line with the problem faced the English materials should get a treatment by English for Occupational Purposes (EOP), in response with the need field of occupation to comprehend in simple instructions, English for computers, operating tools, and, comprehending simple English for speaking, writing and reading textbook. As stated by Kennedy and Bolitho (1984:4) in EOP, English is taught to meet English needs in the area specialization of occupation. Although English can play an important role in their work field then this paper is expected to fill the gap of syllabus by adopting, adapting, and developing the materials in learning English by English for Occupational Purposes (EOP) Kata Kunci: Management, Informatics Computer Academy